1999
DOI: 10.1111/1467-9884.00183
|View full text |Cite
|
Sign up to set email alerts
|

A Distribution-Free Regional Cumulative Sum for Identifying Hyperendemic Periods of Disease Incidence

Abstract: A new distribution-free cumulative sum procedure is introduced. This procedure aims to diagnose geographical±temporal clustering of events in parallel records of events over time in neighbouring geographical areas of a de®ned region or country. The procedure applies in the presence of possible seasonality and yearly trend provided that those patterns are maintained over all the areas of the region. The method is applied speci®cally to records of meningococcal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Holt's method or Double Exponential Smoothing (DES) [18] uses the recursive application of an exponential filter twice and it works using the parameters like the sequence of observations (x t ), the smoothed value (s t ), and the best estimate of the trend (b t ). Equations (12)(13)(14)(15)(16) show the mathematical equations for DES model, where α is the data smoothing factor, with range 0 < α < 1 and β is the trend smoothing factor, with range 0 < β < 1. Equation ( 16) is the forecasting equation with m-steps ahead…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holt's method or Double Exponential Smoothing (DES) [18] uses the recursive application of an exponential filter twice and it works using the parameters like the sequence of observations (x t ), the smoothed value (s t ), and the best estimate of the trend (b t ). Equations (12)(13)(14)(15)(16) show the mathematical equations for DES model, where α is the data smoothing factor, with range 0 < α < 1 and β is the trend smoothing factor, with range 0 < β < 1. Equation ( 16) is the forecasting equation with m-steps ahead…”
Section: Methodsmentioning
confidence: 99%
“…Sparks et al [11] optimized an early outbreak detection of Influenza and Ross River virus using cumulative sum and negative binomial transitional regression. Leung et al [12] developed a distribution-free cumulative sum procedure to diagnose geographical temporal clustering events from over-time neighboring geographical areas. Fisman et al [13] developed an Incidence Decay and Exponential Adjustment (IDEA) model to aid public authorities during the outbreaks or epidemic situations and found that the model provides a more accurate estimate of the total size and duration for a given outbreak when the value of R 0 is low or moderate.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…The CUSUM chart has been used to detect patterns of disease occurrence in the methods developed by Raubertas [9], Rogerson [10], Leung et al [11], and Rogerson and Yamada [12], in addition to the local Knox monitoring method. Joner et al [13] studied the ARL performance for the method developed by Rogerson and Yamada [12], but the performance of the CUSUM chart for monitoring the local Knox statistic has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%